Industrial training report: Hospital Tanah Merah / Nurhasnaa Ramli - Ramli, Nurhasnaa (Perpustakaan Tengku Anis, 2017)
Based on the period from 01 February 2017 to 30 June 2017 in Hospital Tanah Merah (HTM) in department Information Communication and Technology, (ICT). Hospital currently uses a manual system for the management and maintenance of critical information. The current systems require numerous paper forms, with data stores spreads throughout the hospital management infrastructure. Often information is incomplete, or does not follow management standard. Forms are often lost in transit between departments requiring a comprehensive auditing process to ensure that no vital information is lost. Multiple copies of the same information exist in the hospital and may lead to inconsistencies in data in various data stores. A significant part of the operation of any hospital involves that acquisition, management and timely retrieval of great volumes of information. This information typically involves; patient personal information and medical history, staff information and ward scheduling, staff scheduling and various list of other faculties. All of this information must be managed in an efficient and cost wise fashion so that an institution's resources may be effectively utilized HMS will automate the management of the hospital making it more efficient and error free. It aims at standardizing data, consolidating data ensuring data integrity and error free. It aims at standardizing data, consolidating data ensuring data integrity and reducing inconsistencies.